2002
DOI: 10.1084/jem.20011149
|View full text |Cite
|
Sign up to set email alerts
|

Human Dendritic Cells Activate Resting Natural Killer (NK) Cells and Are Recognized via the NKp30 Receptor by Activated NK Cells

Abstract: During the innate response to many inflammatory and infectious stimuli, dendritic cells (DCs) undergo a differentiation process termed maturation. Mature DCs activate antigen-specific naive T cells. Here we show that both immature and mature DCs activate resting human natural killer (NK) cells. Within 1 wk the NK cells increase two– to fourfold in numbers, start secreting interferon (IFN)-γ, and acquire cytolytic activity against the classical NK target LCL721.221. The DC-activated NK cells then kill immature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

40
921
5
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 877 publications
(981 citation statements)
references
References 61 publications
40
921
5
2
Order By: Relevance
“…DefectiveiDC killing and defectivetumor targetcell killing are strictly correlated when reduced NKp30 expression is present in peripheral NK cells [43,44]. The present results therefore indicate that, at least for peripheral NK cells, skewed editing of adaptive anti-HCV immune responses secondary to a defective interaction of NKp30 with its ligand on iDC [19] is unlikely. Rather, increased NK cell interaction with DC via NKp30 could lead to increased production of IL-10 in addition to IFN-c and TNF-a.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…DefectiveiDC killing and defectivetumor targetcell killing are strictly correlated when reduced NKp30 expression is present in peripheral NK cells [43,44]. The present results therefore indicate that, at least for peripheral NK cells, skewed editing of adaptive anti-HCV immune responses secondary to a defective interaction of NKp30 with its ligand on iDC [19] is unlikely. Rather, increased NK cell interaction with DC via NKp30 could lead to increased production of IL-10 in addition to IFN-c and TNF-a.…”
mentioning
confidence: 56%
“…Evidence supports an involvement of innate immune mechanisms in the editing of the adaptive immune response to intracellular pathogens or tumor cells. These mechanisms include, among others, NK cellmediated lysis of immature (but not of mature) DC [17], NK cell-derived cytokine production (notably IFN-c and TNF-a) that supports DC maturation and NK cell activation upon interaction with DC [18][19][20]. The existence of a wide area of interplay between innate and adaptive immunity might therefore influence the outcome (in terms of success or failure) of antiviral or antitumor responses.…”
mentioning
confidence: 99%
“…It was recently shown that DC play an important role in innate immunity, including activation of NK cells [54]. CRP may also play a role in innate responses.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several years, there have been increasing reports of the importance of NK cells in responses in immunotherapy. 2,6,7 Specifically, NK cells have been implicated as having important reciprocal interactions with DC, facilitating collaboration between innate and adaptive immune responses. 4,5 In one carefully studied model of genetic immunization with adenovirally transduced DC that closely resembles our models, antitumor immunity was completely independent of CD8 þ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…2 Subsequent studies have confirmed these observations in human in vitro cell cultures. [3][4][5][6][7] Additional studies focused on the possible role of NK cells in the activation of antigen-specific CTL responses generated by tumorantigen-loaded DC. Studies in both murine and human model systems showed that NK cells contributed to CTL generation.…”
mentioning
confidence: 99%